The way out of gendered poverty? Economic empowerment of young ugandan mothers through NGO support - Emdal, Elisabeth (2016)
Women’s important role in development is widely recognised today, as is their need for empowerment. Many Ugandan women are in a marginalised position because of lack of education, gainful employment, access to health, and inequality of opportunities, resources and rights in society as well as the in household. Combined with traditional gender expectations such as childbearing and domestic duties, women are experiencing adversities and many are living in deep poverty. Having scarce access to financial resources as well as entering into motherhood at an early age means that there are many challenges facing young mothers in Uganda. The aim of this project was to investigate to what extent NGO programmes that are tailored to economically empower young mothers actually benefit them. Many initiatives have been made to enhance women’s employability and economic status, and this study looked at the strategies of the NGO Health Child. The young mothers’ experience of the NGO programme and its immediate benefits as well as long-term impact was thoroughly explored. Fifteen mothers between the ages of 18 to 24 living in the Jinja district, Eastern region of Uganda participated in the research. They provided information through in-depth interviews about their lives before their involvement with Health Child, their experiences of becoming and being beneficiaries, the impact this had on their lives and those of their families, and their plans and hopes for the future. Additionally, three key informants from the NGO were interviewed to provide background information, as well as an organisational and professional perspective. The findings from the research revealed that, although the young mothers had been involved with the NGO programme for varying lengths of time, the majority expressed that it has had a positive impact in their lives. Immediate benefits included being able to afford basic needs for the family, the building of networks and friendships with other beneficiaries and in the community, acquisition of skills and the ability to start planning the future, through for instance starting up enterprises or buying land. It became evident that some of the young mothers had already been able to reap some long-term benefits such as more respect and an improved relationship with their husbands alongside the economic empowerment.